Membangun Loyalitas Karyawan Melalui Kepemimpinan dan Lingkungan Kerja - Petra Arnol Vini Bulunisora Harita; Ray Octafian (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of leadership style and work environment on employee loyalty at PT Sumber Bintang Rejeki, a multinational garment company based in Semarang. The main issue addressed is the limited comprehensive understanding of how these two factors simultaneously impact employee loyalty in labor-intensive garment industries. This research employs a quantitative explanatory approach involving 141 respondents selected using Slovin’s formula. Data were analyzed using multiple linear regression. The results show that both leadership style and work environment have a positive and significant effect on employee loyalty, with the work environment having a more dominant influence. These findings highlight the importance of integrating effective leadership practices with a supportive work environment to enhance employee loyalty. The study contributes to the development of human resource management theory and offers strategic recommendations for employee management in the garment industry. The research is limited by its focus on a single location and a narrow scope of variables, suggesting future studies explore broader variables and settings to deepen insights.